Higher education teachers exploring collaboratively: an experience to improve their practice - Cristina Canabal García; María Dolores García Campos (Universitat Politècnica de València, 2012)
This article studies in depth the Master in Higher Education Teaching, a training proposal with almost 10 years of life and born in the framework of the Training Team of the University of Alcalá (UAH). As an educational experience, it has grown thanks to the participating teachers that have brought it to life, and to the teaching team that has been consolidating throughout this entire time. It began being a 120 hour course and it has become an Official Master's Degree 60 ECTS that has great acceptance and demand both by our teachers and teachers from other universities. On these pages we will analyze what it is about, what are the goals that we set, the competences to be developed, using what methodological strategies we give sense to the course and what are the assessment tools and criteria we use in the development of it. We will stop especially in the teaching team that develops it, both teachers of UAH belonging to different branches of knowledge, as collaborators of other universities and institutions, that they share with us a work philosophy and agree with the initial concepts that give meaning to this training proposal. We will also delve into the working groups that are configured within the course and that we call reflective triads, consisting of the same teachers who participate. The goal of this training strategy is that they experience from an initiative of teaching coordination, the planning and the implementation of integrated and interdisciplinary proposals in order to promote deep and sustainable changes in the University teacher's professional culture.